Two Related RNA-editing Proteins Target the Same Sites in Mitochondria of Arabidopsis thaliana - Verbitskiy, Daniil (American Society for Biochemistry and Molecular Biology, 2012)
The facilitators for specific cytosine-to-uridine RNA-editing events in plant mitochondria and plastids are pentatricopeptide repeat (PPR)-containing proteins with specific additional C-terminal domains. Here we report the related PPR proteins mitochondrial editing factor 8 (MEF8) and MEF8S with only five such repeats each to be both involved in RNA editing at the same two sites in mitochondria of Arabidopsis thaliana. Mutants of MEF8 show diminished editing in leaves but not in pollen, whereas mutants of the related protein MEF8S show reduced RNA editing in pollen but not in leaves. Overexpressed MEF8 or MEF8S both increase editing at the two target sites in a mef8 mutant. Double mutants of MEF8 and MEF8S are not viable although both identified target sites are in mRNAs for nonessential proteins. This suggests that MEF8 and MEF8S may have other essential functions beyond these two editing sites in complex I mRNAs.